PENCEGAHAN COVID-19 DAN PENINGKATAN KESEHATAN ATLET PADA MASA PANDEMI - Albert W Aridan Tangkudung; Iwan Setiawan; Heni Widyaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2021)
Abstract Community Service is one of the pillars of “Tri Dharma” of our National University, “Tri Dharma” contain 3 pillars which is teaching, research and Community Servive. Community service is an integral part of the Tri Dharma of National University which in its implementation cannot be separated from the other two dharmas and involves the entire academic community: lecturers, students, education staff and alumni. The results of the discussion of the webinar with the title